Poetry, Art, and the Anthropocene: Susan Schuppli and Kacper Bartczak - Kałuża, Anna (Porównania, 2022)
The aim of the article is to outline the basic critical possibilities that visual and linguistic art can have in the world of anthropocene. Referring to, among other things examples of the so-called slick images by Susan Schuppli and poems by Polish poet Kacper Bartczak I look at images in digital and poetic media. I am interested in the differences between an artistic activity in which inhuman actors play an important role and one in which the main initiator is still a human being, trying to place human language and human artifacts in the network of biological-technological transformations.